OPTIMALISASI PROSES TRANSESTERIFIKASI DALAM PEMBUATAN BIODIESEL DARI MINYAK JELANTAH MENGGUNAKAN KATALIS KALSIUM OKSIDA - Ronan Fadly Qoshiro; Yohandri Bow; Rima Daniar (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2026)
Used cooking oil is household waste that is often disposed of directly into the environment, thus potentially polluting water and soil. On the other hand, used cooking oil contains triglycerides which can still be used as raw material for biodiesel through the transesterification process. The global energy crisis and increasing awareness of the environmental impact of fossil fuels have driven the development of biodiesel as an environmentally friendly and renewable alternative energy source. This study aims to optimize the process parameters for making biodiesel based on used cooking oil using calcium oxide (CaO) catalyst with a concentration of 0.5 N. The research variations included reaction times of 40, 60, and 80 minutes and stirring speeds of 200, 300, and 400 rpm at a reaction temperature of 50 °C and a molar ratio of methanol to oil of 6:1. The results showed that reaction time and stirring speed significantly influenced the yield percentage and quality of biodiesel. The optimum conditions were obtained at a reaction time of 40 minutes and a stirring speed of 400 rpm, with a yield of 82.61%. The resulting biodiesel has physical characteristics according to SNI 7182:2015 standards, including a density of 870–889 kg/m³, a viscosity of 0.30–0.41 cP, a flash point above 139 °C, and a cetane number of up to 51.1. This indicates that the use of CaO catalyst is effective in improving the performance of the transesterification reaction and producing good-quality biodiesel. Furthermore, operational parameters such as reaction time and stirring speed have been shown to play a critical role in determining conversion efficiency and biodiesel quality. Overall, this research confirms the potential of used cooking oil as an economical renewable energy source and an environmental solution for waste management. The process also has the potential to be further developed for larger- scale production and community applications.